193 A Novel First in Class IKK Alpha Inhibitor Abrogates Endothelial Cell Nuclear Factor Kappa B Signalling and Inflammatory Protein Expression. (31st May 2014) - Ka Ho, Ho; Plevin, Robin; Mackay, Simon; Paul, Andrew
Abstract : Introduction: Up-regulation of nuclear factor kappa B (NF–B), has been strongly implicated in cardiovascular disease. 1 Two main pathways operate to regulate the activation of different NF–B species; the canonical or classical NF–B (p65) pathway regulated exclusively by inhibitory kappa B kinase beta (IKKβ) and the non-canonical NF–B pathway driven by IKKα. The majority of studies have focussed on IKKβ inhibition in combating endothelial inflammation, however IKKβ inhibition also promotes apoptosis of endothelial cells. 2 We have therefore examined the potential of selective IKKα inhibition as a novel therapeutic target. To this end we have developed the first selective IKKα inhibitor (SU1261) and tested it on endothelial cells. Methods: HUVECs (passage 3–6) were used for the study. Western blotting was used to asses pathway activation (non-canonical; pp100, p52, canonical; I–Bα, pp65), whilst qRT-PCR and Western blotting to assay inflammatory protein expression. Motility was assessed using a wound healing assay. SU1261 and SU1266 were synthesised in-house as part of a CRUK small molecule drug discovery programme (PI Professor Simon MacKay). Results: Endothelial cells stimulated with LIGHT (1ng/ml) or overexpression of NF–B-inducing kinase (NIK 50pfu), the upstream regulator of IKKα, increased the phosphorylation of p100 and the formation of p52 NF–B, two non-cannonical pathway markers. Both parameters were inhibited by siRNA for IKKα. These responses where inhibited in a concentration dependent manner by SU1261 (0.3–3.0 microM) and also the non-selective inhibitor SU1266. However, SU1266 reversed two responses indicative of IKKβ inhibition; the loss of I–B and the phosphorylation of p65 NF–B. In contrast, SU1261 was without effect at concentrations up to 30μM indicating selectivity for IKKα. In addition, SU1261 was without effect on agonist mediated activation of MAP kinase signalling. Furthermore, SU1261 also reduced the expression of ICAM-1 and VCAM-1, two genes dependent on both IKKα and β, and inhibited the expression of CXCL12, a pro-angiogenic factor dependent on IKKα function. In contrast, SU1266 caused a marked increase in expression of CXCL12. Finally, SU1261 also strongly inhibited the motility of endothelial cells in wound healing assays (10μM of SU1261 induced 80% of the inhibitory effect). Conclusions/implications: These studies reveal for the first time the potential of IKKα inhibition as a new therapeutic target for vascular disease. Drugs of this nature will circumvent the limits imposed by selective IKKβ inhibition. Reduced gene expression and motility may also implicate use in the control of angiogenesis. Acknowledgements: This work was sponsored by the British Heart Foundation and CRUK. References: Pamukcu B, Lip GY, Shantsila E. Thromb Res 2011;128:117–123 Al-Mutairi M, Al-Harthi S, Cadalbert L, Plevin R. Br J Pharmacol 2010;161:782–798